Strategic electromagnetic interferences suppression in boost converters: zero-switch techniques - M'barki, Zakaria; Ait Salih, Ali; Mejdoub, Youssef; Senhaji Rhazi, Kaoutar (International Journal of Advances in Applied Sciences, 2024)
This article delves into the growing demand for efficient power conversion technologies accompanying the rise in electric vehicle (EV) adoption. Boost converters, essential for increasing the battery pack voltage to propel EV motors, pose a challenge due to the electromagnetic interference (EMI) generated by the high switching frequency of power devices. To address this issue, practitioners employ zero-voltage switching (ZVS) and zero-current switching (ZCS) techniques. In this comparative study, we systematically evaluate the effectiveness of these soft switching techniques in reducing conducted EMI in boost converters designed for EV applications. The results illuminate the potential of both ZVS and ZCS in significantly mitigating EMI emissions when compared to conventional hard-switching methods. Notably, ZVS soft switching emerges as more efficient and effective, particularly under higher loads, while ZCS soft switching excels in reducing EMI at lighter loads. In conclusion, the study asserts that ZVS soft switching presents a more promising solution for curtailing conducted EMI in boost converters for EV applications, particularly in high-load scenarios. However, it underscores the importance of considering specific operational conditions when deciding between the two techniques.